Enhancement of luminescence of quantum emitters in the epsilon-near-zero waveguide - So, Jin-Kyu (2021)
We report a resonant enhancement of luminescence intensity from an ensemble of CdSe/ZnS quantum dots embedded in a nanoscale rectangular photonic waveguide operating in the cutoff regime and therefore experimentally demonstrate the recently predicted phenomenon of increase in the emission rate of an ensemble of quantum emitters in the epsilon-near-zero environment.